Eupatilin Ameliorates Lipopolysaccharide-Induced Acute Kidney Injury by Inhibiting Inflammation, Oxidative Stress, and Apoptosis in Mice - Kiryeong Kim; Hyo-Lim Hong; Gyun Moo Kim; Jaechan Leem; Hyun Hee Kwon (Current Issues in Molecular Biology, 2023)
Acute kidney injury (AKI) is a common complication of sepsis. Eupatilin (EUP) is a natural flavone with multiple biological activities and has beneficial effects against various inflammatory disorders. However, whether EUP has a favorable effect on septic AKI remains unknown. Here, we examined the effect of EUP on lipopolysaccharide (LPS)-evoked AKI in mice. LPS-evoked renal dysfunction was attenuated by EUP, as reflected by reductions in serum creatinine and blood urea nitrogen levels. LPS injection also induced structural damage such as tubular cell detachment, tubular dilatation, brush border loss of proximal tubules, and upregulation of tubular injury markers. However, EUP significantly ameliorated this structural damage. EUP decreased serum and renal cytokine levels, prevented macrophage infiltration, and inhibited mitogen-activated protein kinase and NF-κB signaling cascades. Lipid peroxidation and DNA oxidation were increased after LPS treatment. However, EUP mitigated LPS-evoked oxidative stress through downregulation of NPDPH oxidase 4 and upregulation of antioxidant enzymes. EUP also inhibited p53-mediated apoptosis in LPS-treated mice. Therefore, these results suggest that EUP ameliorates LPS-evoked AKI through inhibiting inflammation, oxidative stress, and apoptosis.